2016
DOI: 10.5483/bmbrep.2016.49.10.097
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of UV-induced nucleotide excision repair activity upon forskolin treatment is cell growth-dependent

Abstract: Forskolin (FSK), an adenylyl cyclase activator, has recently been shown to enhance nucleotide excision repair (NER) upon UV exposure. However, our study revealed that this effect was detected in human skin epithelial ARPE19 cells only in growing cells, but not in non-cycling cells. When the cells were grown at low density (70% confluence), FSK was capable of stimulating cAMP responsive element binding (CREB) phosphorylation, a marker for FSK-stimulated PKA activation, and resulted in a significant increase of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Following DNA damage, a cellular defense is mounted in order to maintain genomic integrity, including nucleotide excision repair. The 6-4PP photoproduct is repaired only by nucleotide excision repair in human keratinocytes [62,63,83]. A complete repair of 6–4PP was observed in previous studies with synthetic compounds not related to vitamin D 3 [84,85].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Following DNA damage, a cellular defense is mounted in order to maintain genomic integrity, including nucleotide excision repair. The 6-4PP photoproduct is repaired only by nucleotide excision repair in human keratinocytes [62,63,83]. A complete repair of 6–4PP was observed in previous studies with synthetic compounds not related to vitamin D 3 [84,85].…”
Section: Discussionmentioning
confidence: 79%
“…6-4PP is a crucial product of UVB-induced damage to human keratinocytes that is removed through the nucleotide excision repair pathway [3,[62], [63], [64]]. The repair activity resulting in 6-4PP removal was measured to evaluate the photoprotective effects of all compounds under study on UVB-irradiated keratinocytes.…”
Section: Resultsmentioning
confidence: 99%
“…When cells were cultured at low density, FSK stimulated cAMP responsive element binding (CREB) phosphorylation, which is a marker of PKA activation, producing a significant increase in the activity of NER compared to the control. These findings indicate that cell growth is critical for FSK to improve NER function and suggest that cell growth conditions should be considered as a variable while evaluating the FSK efficacy in inhibiting UVR-induced photodamage ( 96 ). FSK has been used orally for non-skin-related therapeutic uses, but not in skin disease ( 168 ).…”
Section: Dietary Botanicals (Table 3 )mentioning
confidence: 99%
“…It is a classical activator of the adenylate cyclase enzyme resulting in elevated levels of cyclic adenosine monophosphate (cAMP). A recent study addressing the effect of FSK in UVR-mediated photodamage reported that FSK accelerated the removal rate of UVR-induced photolesions in vitro and in vivo ( 96 ). Topical application of forskolin also restored pigmentation UVR-independent in an MC1R-defective fair-skinned animal model ( 165 ).…”
Section: Dietary Botanicals (Table 3 )mentioning
confidence: 99%